(NdUALXNYJ @NIONIZM KAK PARADIGMALXNYJ KONCEPT METAFIZIKI (B:s ((NrAS[IRENNYE PREZENTACIONNYE PRINCIPY(B) /s - (NkARAPETQN(B, (NfELIKS aSKANAZOWI^s ((NeREWAN (B:s (NaWTORSKOE IZDANIE(B,s, 2020)
Summary (NS(B. 348 (NNA ANGL(B. (NQZ(B.s
(NbIBLIOGR(B.: (NS(B. 199-201 s
Keywords: (NfILOSOFIQs; (NrELIGIQs; (NmIFOLOGIQs; (NpARADIGMAs